The first definitive record of the giant larvacean, Bathochordaeus charon, since its original description in 1900 and a range extension to the northeast Pacific Ocean. Issue 1 (December 2016) - Sherlock, R.; Walz, K.; Robison, B.
Abstract Background Larvaceans in the genusBathochordaeus are large, often abundant filter feeders found throughout much of the world ocean. The first described species, Bathochordaeus charon, was reported over 100 years ago by Chun. However in the time since, few specimens have matched Chun's original description, resulting in ambiguity on the validity ofB. charon as a species. Methods Specimens ofBathochordaeus charon were identified based on morphological traits, molecular data and observations made on high definition video. Results The first records ofBathochordaeus charon from the northeast Pacific Ocean off central California and Oregon, USA are reported. Morphology and molecular data clearly distinguishB. charon from its congener, B. stygius . Conclusions This paper establishes the first review ofBathochordaeus charon since its original description, extends the range of this species to the northeast Pacific Ocean, and provides the first molecular evidence for two species ofBathochordaeus .